ANGIOTENSIN RECEPTOR-NEPRILYSIN INHIBITOR SUPPRESSED CARDIAC DYSFUNCTION BY ANGIOGENESIS IN MICE MODEL OF ATHEROSCLEROSIS. (April 2021) - Suematsu, Yasunori; Ideishi, Akihito; Tashiro, Kohei; Miura, Shin-Ichiro
Abstract: Objective: We previously reported that Angiotensin receptor-neprilysin inhibitor (ARNI) has the effects of suppression of myocardial hypertrophy and fibrosis in addition to reduction of afterload by natriuretic effect. We investigated the effects of ARNI against mice model of atherosclerosis. Design and method: Atherosclerotic model was induced by high cholesterol diet for 4 weeks to apolipoprotein E knockout mice. We divided into four groups: no treatment (CTL), valsartan 30 mg/kg (VAL), sacubitril (neprilysin inhibitor) 30 mg/kg (SAC), and ARNI 60 mg/kg for additional 13 weeks. Results: Body weight and systolic blood pressure in the VAL, SAC and ARNI groups did not show significant differences compared to those in the CTL group. Serum brain natriuretic peptide (BNP) in ARNI group (605 ± 221 pg/ml) was significantly increased than that in VAL (391 ± 57 pg/ml) and SAC (357 ± 91 pg/ml) groups, but not CTL group (393 ± 192 pg/ml). Although the rate of atherosclerotic area in aorta was 16.3 ± 5.8 % after treatment, there were no significant differences between the groups. In the CTL group, left ventricular ejection fraction (LVEF, 81.6 ± 4.8 %) and fractional shortening (FS, 44.8 ± 5.8 %) at baseline were significantly reduced after treatment (67.8 ± 8.2 % and 33.3 ± 6.1 %). Interestingly, LVEF (76.6 ± 6.7 %) and FS (40.1 ± 6.1 %) after treatment in the ARNI group were significantly preserved compared to those in the CTL group. In real time polymerase chain reaction analysis of LV after treatment, relative mRNA expression of BNP and angiogenetic factors including ATPase sarcoplasmic/endoplasmic reticulum Ca transporting 2, vascular endothelial growth factor A, cluster of differentiation 34 in ARNI group were significantly increased than those in the CTL group. Conclusions: Although ARNI did not suppress atherosclerosis in mice, it preserved LVEF via improving angiogenetic ability.